Lebenserinnerungen : die unvollendete Autobiographie einer frauenbewegten Pazifistin - Stöcker, Helene 1869-1943 (L' homme <Köln> / Archiv, 2015)
Memoirs (unfinished) of Helene Stöcker (1869-1943), women's rights activist, pacifist and social reformer